Evaluation the Lesson Plan of English Language Learning in Junior High School, Seraphine Bakti Utama West Jakarta - Mauliate, Hendrico Dolok; Rahmat, Aceng; Wachidah, Siti (International Journal of Scientific Research and Management (IJSRM), 2019)
The study aims to evaluation the lesson plan of english language learning. This research was conducted at the Junior High School, Seraphine Bakti Utama West Jakarta. The research methodology used is evaluative through the flow of the gap model (discrepancy evaluation model). Data collection through interviews, document tracing, and observation. Key informant is the principal, teacher, and student. The results showed that: (1). The use of the lesson plan drafting principles occurs a negative (-) gap that resides in the quadrant (-2) because it earns a value of 40%, particularly on the full aspects of the basic competency of spiritual attitudes, attitudes Knowledge and skills, centered on students, context, kinship, feedback and alignment. (2). The implementation of lesson plan preparation of the (+) gap occurred at the Quadrant (2) because it gained a value of 60%, especially in the aspect of syllabus assessment, and the development of learning assessments. (3). In the implementation of lesson plan there is a negative positive (-) gap that resides in the quadrant (-2) because it has a value of 40%, especially in the introduction of activities, core activities and closures. In conclusion, the preparation of lesson plan should refer to Permendikbud No. 103 year 2014 about learning in primary education and secondary education.